Flame characteristics and burning rate of small pool fires under downslope and upslope oblique winds. (15th November 2016) - Zhu, P.; Wang, X.S.; He, Y.P.; Tao, C.F.; Ni, X.M.
Highlights: Burning rates under upslope wind reduce more obviously than that under downslope wind. Inverse variations of flame shape occur between upslope and downslope wind. Flame lengths first increase, then decrease with increasing wind speed. Flame tilt angle increases until to an asymptotic value with increasing wind speed. The modified correlations are presented to describe the flame tilt characteristics. Abstract: This paper presents an experimental investigation on burning rate, flame tilt angle and flame length of small ethanol pool fires under different oblique winds. Square pool fires with dimension of 4 cm and 6 cm with wind attack angles from 0° to 30° and wind speeds from 0 to 3.28 m s −1 for downslope airflow and from 0 to 1.90 m s −1 for upslope airflow are tested. Flame tilt angle and flame length are determined based on luminous flame intermittency from the flame images. The results show that the burning rate under downslope wind is relatively larger than that under upslope wind at the same absolute wind speed and slope angle. The flame tilt angle and flame length generally increase with the increase of wind slope angle for downslope airflow, but decrease with the increase of upslope airflow angle. At a given wind slope angle, the flame tilt angle generally increases with the increase of wind speed until to an asymptotic value when the wind speed exceeds 0.35 m s −1 ; the flame length first increases and then decreases for downslope wind, but initially decreases then increases before decrease again for upslope wind. In addition, some modified correlations are developed to analyze the flame tilt angle and flame length data under oblique wind conditions.